Asplenium appressifolium (Aspleniaceae), a new species from Thailand. (2nd December 2021) - Petchsri, Sahanat; Boonkerd, Thaweesakdi
Abstract : Asplenium appressifolium Boonkerd & S. Petchsri, a new lithophytic fern species from Surat Thani province, Peninsular Thailand, is described and illustrated. The affinities with the similar species A. crinicaule Hance, A. pellucidum Lam. and A. tenerum G. Forst. are discussed.